FIGHTER PLANE ONLINE GAME BASED ON DESIGN SCIENCE RESEARCH METHODOLOGY USING SOCKET.IO AND NODEJS - I Putu Agus Eka Pratama; I Wayan Gus Arisna (Indonesian Journal of Engineering and Science (IJES), 2022)
Computer networks are growing rapidly from time to time, making the internet, websites, web programming languages, and socket programming increasingly used in the provision of information technology-based applications and services. One of them is the availability of web-based online game multiplayer applications involving several players. This paper presents the research results in the form of designing and implementing an online game based on socket programming fighter aircraft on a computer network with a client-server paradigm. This research uses DSRM (Design Science Research Methodology) with seven sequential steps. Game applications are designed using Use Case Diagrams and implemented using JavaScript, Socket.io, and NodeJS. Application testing uses Black Box Testing and User Acceptance Testing (UAT). The results of Black Box Testing show that all features and menus in the game application can run well. In contrast, the results of the UAT with a total of 100 respondents indicate that 60% of respondents said the game was very easy to use, 30% said it was easy to use, and 10% said it was difficult to use.